MEDB-16. Persistent radiological lesions at the end of primary therapy in childhood medulloblastoma: residual lesion or active residual tumor?. (3rd June 2022) - Schömig, Lena; Obrecht, Denise; Mynarek, Martin; Bison, Brigitte; Schwarz, Rudolf; Pietsch, Torsten; Rutkowski, Stefan; Benesch, Martin
Abstract: BACKGROUND: Magnetic resonance imaging (MRI) of patients with medulloblastoma (MB) often shows persistent residual findings after primary treatment. Criteria for characterizing these lesions and consensus on further therapeutic approaches are not established. MATERIAL AND METHODS: Eighty-four patients ≥4 years with centrally reviewed residual lesions on MRI at the end of primary therapy with initial surgery between 2000 and 2018 were identified. Data were extracted from the German HIT-MED database. RESULTS: Median age at initial diagnosis was 9.3 (4.0-20.8) years. 91.7% were histologically classified as CMB, 7.1% as LC/AMB and 1.2% as DMB. The majority (65.5%) of the evaluated cohort was assigned to molecular subgroup 4, 24.1% to group 3, 6.8% to WNT, 3.4% to SHH. Median follow-up for survivors was 5.96 (1.41-16.67) years. Univariate analysis revealed that patients showing an overall partial response (PR) to primary therapy have a significantly lower risk of progression of residual lesions compared to patients with stable disease (SD) (5-year PFS [PR]: 62.5±7, 0; 5-year PFS [SD]: 35.9±12.8; 5-year OS [PR]: 85.6±5.1; 5-year OS [SD]: 54.1±13.7; p=0.02 [PFS], p=0.04 [OS]). Additionally, patients with multiple residual lesions (M+ and R+) were at higher risk of progression (5-year PFS [R+ only]: 72.4±12.0, 5-year PFS [R+/M+]: 22.9±17.9; p=0.02 [PFS]). Further procedures after the end of primary therapy (additional resections, chemotherapy, radiotherapy) did not impact on PFS and OS. These results were confirmed by multivariate Cox regression. For molecular or histological type no significant effect was found, presumably due to small cohort. CONCLUSION: PFS in patients with residual lesions at the end of primary treatment depends on the overall response to primary therapy. Additional procedures do not seem to be superior compared to watch-and-wait strategies. Decisions regarding further therapies should be scrutinized on a case-by-case basis. Further identification of biomarkers is warranted.